Imaging Features and Treatment Options for Breast Pseudoaneurysms After Biopsy: A Case‐Based Pictorial Review. (29th June 2019) - Adler, Kalie; Samreen, Naziya; Glazebrook, Katrina N.; Bhatt, Asha A.
Abstract : Pseudoaneurysm (PSA) formation is a potential complication of breast biopsies. Ultrasound is the most common imaging modality used for evaluation and treatment of a PSA. Color Doppler images show a cystic structure with swirling flow inside in a "to‐and‐fro" pattern. Treatment options for PSA include observation, ultrasound‐guided focused compression, thrombin injection, open surgical repair, and percutaneous embolization. The risks and benefits of these treatment options will be discussed in the following cases.